Resilience-oriented repair crew and network reconfiguration coordinated operational scheduling for post-event restoration - Zhou, Fuju; Zhou, Peng; Shi, Tianchen; Jing, Jiangping; Liang, Gaige; Xu, Shengrong; Zhou, Jianda; Yang, Kai (Frontiers in Energy Research, 2024)
This paper introduces a post-disaster load restoration approach for the distribution grid, utilizing network reconfiguration (NR) and repair crews (RCs) dispatching to significantly enhance grid resilience. We propose a RC-NR coordinated model that leverages diverse flexible resources within the active distribution network, aimed at not only enhancing the grid's resilience level but also efficiently mending the fault lines. The model introduces fault repairing and sequential NR coupled constraints to devise an optimal resilience strategy within the temporal domain cooperation, focusing on minimizing repair and penalty costs associated with the restoration process. To tackle the challenge of computational complexity, the nonlinear model is reformulated into a mixed integer second-order cone programming model. The approach's efficacy is validated through case studies on an IEEE 33-bus system, where simulation results demonstrate a considerable improvement in grid resilience, achieving optimal load recovery with reduced restoration times and costs. The proposed approach outperforms traditional methods with optimal repair sequence and RCs scheduling, aligned with NR efforts, contribute to an improved system resilience level.